Mechanics today. - Nemat-Nasser, Siavouche (Pergamon mechanics today series., 1976)
Mechanics Today, Volume 3 provides the advances in the fields of solid and fluid mechanics and applied mathematics. This volume is divided into six chapters that discuss the fundamentals and analytical and experimental results of dynamic behavior of linear and nonlinear systems. Chapter I provides a formulation of the effective stiffness theory with equations of motion and boundary conditions presented for the case of plain strain motion. Chapter II summarizes some of the analytical results that have been obtained in an effort to improve understanding of elastodynamic fracture processes. Chapt.